FEATURES TEACHING HISTOLOGY, CYTOLOGY AND EMBRYOLOGY OF THE STUDENTS IN THE SPECIALTY "LABORATORY DIAGNOSTICS" - Евтушенко, В.М. (World of Medicine and Biology, 2015)
Introduction. In the process of integration of modern Ukrainian system of higher medical education to the European standards are faced with new challenges and conditions for the preparation of highly qualified specialists in "Laboratory diagnosis", due to increased demands for quality and reliability of laboratory research and development of modern laboratory methods for diagnosis of pathological conditions. The aim of the work was to analyze the level of existing methods of teaching the discipline histology, cytology and embryology to prepare students for the specialty "Laboratory diagnosis" and ways to optimize them within the credit-modular system. Materials and methods. As a criterion for assessing the level of training of students and optimization methodological approach to teaching the course "Histology, cytology and embryology" were used survey methods and questionnaires of students and generalization of experience of the faculty of the department. Results and discussion. The educational process is aimed at achieving the learning objectives are formulated in a specialist qualification characteristics and are in the development of their corresponding training content. Given a decade of experience teaching students of this specialty at the Department of Histology, Cytology and Embryology, the curriculum changes in organizational, technical capabilities of the department, areas of research at the university, but in general consistent with the ultimate goals of educational qualification characteristics and educational and vocational programs. Due to the nature of work of specialists in this specialty, in the work program at the rate of histology, cytology and embryology several extended series of lectures and workshops on topics: cytology, blood and blood forming organs, organs of hematopoiesis and immune system. It is also advisable expansion cycle of lectures and workshops on topics: epithelial and connective tissue, digestive and respiratory system, endocrine system, the organs of the urogenital system. Features of teaching material for future specialists include emphasis on laboratory diagnostics, namely in teaching the topic "research methods in histology" dominated situational problems hematological research methods; In studying the topic "blood", each student must prepare an abstract on the topic of this section, as well as learn how to differentiate the cells in blood smears stained with hematoxylin and eosin, and specially made clinical smears stained by the method Romanovsky-Giemsa. Therefore stressed the need to optimize the teaching methods of histology, cytology and embryology for students enrolled in the specialty "Laboratory diagnosis" with the modern requirements. Solutions to this problem - to increase the motivation of students in the learning process, in the development of students' clinical thinking elements. To increase the interest of students asked to provide an opportunity to get extra points for the discipline through independent study and other activities of students. To improve the quality of students in the conditions of credit-modular system also proposed to align with the requirements of the Bologna system, the number of students in groups. Due to the fact that a large part of the curriculum is given to the self-study material for students enrolled in the specialty "Laboratory diagnostics", increased the number of visual aids (electronic atlases, photographs micropreparations, histological terminology dictionaries, multimedia content, videos). Conclusions. The introduction of credit-modular system in the practice of domestic medical institutions was the impetus to activate all areas of teaching work: developing new programs in the discipline, the creation of a standardized way to control the students' knowledge, a more careful selection of educational material, the development of an optimal sequence of its presentation, negotiation training course with related disciplines. Prospects for further research. In the context of the organization of educational process on credit-modular training system it is advisable to introduce innovative methods of classroom students enrolled in the specialty "Laboratory diagnostics".
Keywords: histology; student; laboratory diagnostics